Social Media Practices among HUMSS Students in a Private School in Cabuyao City - Dicolen, Jerome T. (International Journal on Integrated Education, 2025)
This study evaluates the social media practices of HUMSS students from a private school in Cabuyao City through examinations of fact-checking and personal data protection and digital footprint awareness. Students face challenges in information management and privacy protection and online identity maintenance because social media platforms including Facebook, Instagram and TikTok have gained widespread popularity. The research bases its framework on Levine’s Truth-Default Theory and Westin’s Privacy Theory and Meckin’s Digital Footprint Management Theory. The research design uses quantitative methods while collecting data through a structured survey instrument. The assessment of students' knowledge and practices uses descriptive statistics to analyze data that compares results based on student age, gender and socio-economic status. The research findings demonstrate that students demonstrate average knowledge about fact-checking and privacy controls yet they struggle with proper information analysis and digital footprint management. The study demonstrates that schools should teach digital literacy as a curriculum subject to enhance students' responsible social media use abilities. The research contributes to digital citizenship discussions while providing educational and policy recommendations for meeting student digital literacy needs in the twenty-first century.